Сontemporary Medical Decision Support Systems Based on Artificial Intelligence for the Analysis of Digital Mammographic Images - V. A. Solodkiy; A. D. Kaprin; N. V. Nudnov; N. V. Kharchenko; O. S. Khodorovich; G. M. Zapirov; T. V. Sherstneva; Sh. M. Dibirova; L. B. Kanakhina (Вестник рентгенологии и радиологии)
The relevance of implementing artificial intelligence (AI) technologies in the diagnosis of breast cancer (BC) is associated with a continuing high increase in BC incidence among women and its leading position in the structure of cancer incidence. Theoretically, using AI technologies is possible both at the stage of screening and in clarifying BC diagnosis. The article provides a brief overview of AI systems used in clinical practice and discusses their prospects in BC diagnosis. Advances in machine learning can be effective to improve the accuracy of mammography screening by reducing missed cancer cases and false positives.